Sustainable high strength, high ductility engineered cementitious composites (ECC) with substitution of cement by rice husk ash - Zhang, Zhigang (2022)
Generally high strength engineered cementitious composites (ECC) requires high cement content, which is negative to its sustainability as the cement production contributes as much as 8% of global CO2 emissions. To deal with this issue, a sustainable ECC was designed using rice husk ash to partially replace cement up to 40%. Experimental results presented that the compressive strength of the newly designed ECC at 28 days increased from 80 MPa to 111 MPa in spite of diminished cement content. Furthermore, the tensile strain capacity of ECCs increased significantly by forming more micro-cracks as the cement replacement ratios increased. As a side effect, it also reduced the tensile strength of ECCs, which is nevertheless greater than that of conventional C90/105 concrete. At micro-scale, incorporating RHA into ECCs lowered the matrix toughness, yet just reduced the matrix/fiber interfacial bond slightly, as a result, increased PSH index, which well agrees the enhancement of strain capacity of ECCs at composite level. The current results are expected to guide the design of high strength ECC with efficient cement use, and make ECC more sustainable.